Implikasi Disharmonisasi Undang-Undang Peradilan Tata Usaha Negara Dan Undang-Undang Pelayanan Publik - Riza, Dola (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
The decision of the administrative court implemented by unplugging and/or issue a decision on stateadministration. The activity in the law on public service known as administrative services. Nevertheless, there is still a lot going on maladministration inthe implementation of the decision of the administrativecourt. The problem in this research is What are the implications of the disharmonization of the State Administrative Courts Law and the Public Services Law.Legal data used primary legal data, legal data secondary and tertiary legal data. Legal data collection techniques used are the study documents. Legal data analysis technique used is the tecnique of qualitative analysis.based on the results of this study concluded that Based on the results of the research and discussion carried out by the author, the following conclusions can be drawn: Administrative services to implement decisions of the State Administrative Court do not meet the indicators of good public service and have implications in various aspects, including: first, administrative services to implement decisions of the State Administrative Court are difficult to implement quickly and easily.second, the low level of responsibility of state administrative agencies or officials to implement court decisions voluntarily.third, there is no certainty of time for the plaintiff to obtain administrative services in implementing the State Administrative Court's decision quickly and easily.